The Influence of Seedling Age And Dosage of Phosphate Fertilizer on Rice Harvest Result (Oryza sativa L.) - zainol arifin; Ida Sugeng Suyani; Susilo Ribut Anggarbeni (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
This research aims to determine the effect of seed age and phosphate fertilizer dosage on rice yields. The research used a factorial Randomized Group Design (RAK) with two factors and three replications. The first factor is seed age (B) consisted of 4 levels, namely B1 = 15 HSS, B2 = 20 HSS, B3 = 25 HSS and B4 = 30 HSS, while the second factor is the use of phosphate -36 (P) with 3 levels, namely P1 = 50 kg/ha SP-36 equivalent to 5 grams/plot, P2 = 100 kg/hectare SP-36 equivalent to 10 grams/plot and P3 = 150 kg/ha SP-36 equivalent to 15 grams/plot. As a result, there are 12 treatment combinations were obtained. The results of the research showed that the B1 seedling age treatment (15 HSS) was significantly different and consistently obtained the highest results of number of tillers per hill (27), number of productive tillers (22.78), panicle length (24.58 cm). Meanwhile, the P3 Phosphate fertilizer treatment (150 kilograms/ha SP-36) was significantly different and consistently obtained the highest yield of number of productive tillers (21.75), flowering age (21.75 days), number of grains per panicle (166.08 grains), weight of grain per hill (78.78 grams), and weight of 1000 grains (4.01 grams).